ANALISIS KESALAHAN BERBAHASA INDONESIA DALAM TATARAN SINTAKSIS PADA TEKS PIDATO SISWA KELAS X PERAWAT 1 SMK KESEHATAN NUSANTARA SURABAYA - Alfionita , Novia; Ton, Eka Yanti; Alyadi, Raja Afrenra Citra (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2020)
Language as the most important communication tool in human life. Humans can continue to live well and in order with language. Without language everyone will find it difficult to express opinions, ideas, or ideas that they are thinking about. Starting from this, researchers felt interested in examining the speech text of class X Nurse 1 at Nusantara Health Vocational School Surabaya in the syntactic level. The method used in this research is descriptive qualitative method. While the data collection methods in this study include (1) the listening technique, and (2) the note taking technique. While the data analysis in this study is by the method of covering (1) the basic technique of the BUL technique, (2) the advanced technique of fade technique, the dressing technique. The results of this study yaity (1) Language errors in the structure of sentences there are 10 data language errors in sentence structure divided into subject errors (S) of 4 errors, predicate (P) 4 errors, subject and predicate (SP) 1 error, and subjects, predicate, complement (SP Pel) 1 error in the speech text of class X Nurse 1 of SMK Health Nusantara Surabaya, (2) Language errors in the use of particle accuracy there is only 1 error of particle accuracy in speech text of class X Nurse 1 of SMK Health Nusantara Surabaya, including: particle accuracy